Treatment Outcome and Root Canal Preparation Techniques: 5-Year Follow-Up - John O. Makanjuola; Olabisi H. Oderinu; Donna C. Umesi (Elsevier, 2022)
ABSTRACT: Objective: This study aims at comparing treatment outcome and tooth survival of root canal-filled teeth following manual vs rotary instrumentation techniques over a 5-year period. Methods: This was a single-centre study conducted as a follow-up to a short-term parallel-arm randomised controlled noninferiority trial in which root canal treatment was performed on teeth using either rotary or manual instrumentation. Patients were monitored at post 6-month, 1-year, 4-year, and 5-year review periods by blinded evaluators. Treatment outcome was categorised as favourable, uncertain, and unfavourable (employing European Society of Endodontology categorisation based on strict clinical and radiographic criteria), and 5-year tooth survival was determined by assessing whether tooth was in situ in the oral cavity or extracted. The Kaplan-Meier method and log rank test evaluated tooth survival. P value <.05 was considered statistically significant. Results: Ninety of 120 treated teeth were assessed in 37 men and 40 women with mean age of 30.6 ± 10.99 years. Treatment outcome was significantly more favourable in the rotary group compared to the manual group at post 6-month (P = .021) and 1-year (P = .043) review periods. The differences in favourable outcome (P = .498) and tooth survival (P = .296) between the 2 groups were, however, not significant at the 5-year review period. Conclusions: The rotary instrumentation technique was shown to be more effective in resolving clinical symptoms and promoting periapical healing after the post 6-month and 1-year review compared to the manual instrumentation technique; however, both groups had similar favourable outcomes and survival rates after an extended 5-year review period.